An Interest Rate Defense of a Fixed Exchange Rate? - Jeanne, Olivier (IMF Working Papers; Working Paper ;, 2000)
Defending a government's exchange-rate commitment with active interest rate policy is not an option in the Krugman-Flood-Garber (KFG) model of speculative attacks. In that model, the interest rate is the passive reflection of currency-depreciation expectations. In this paper we show how to adapt the KFG model to allow for an interest rate defense. It is shown that increasing the domestic-currency interest rate makes domestic assets more attractive according to an asset substitution effect, but weakens the domestic currency by increasing the government's fiscal liabilities. As a result, raising the interest rate hastens the speculative attack when speculation is motivated by underlying fiscal fragility.